2020
DOI: 10.1007/s12571-020-01078-z
|View full text |Cite
|
Sign up to set email alerts
|

“Informal” food traders and food security: experiences from the Covid-19 response in South Africa

Abstract: This opinion piece looks at the substantial role of informal traders in ensuring food security, and other economic and social goods in South Africa and how they have been impacted by Covid-19 and responses to it. The state responses have reflected a continued undervaluing and undermining of this sector to the detriment of the traders themselves, their suppliers, and their customers. There is a need for a new valuing of the sector that would recognise and build on its mode of ordering and key contributions to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
79
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 5 publications
0
79
0
1
Order By: Relevance
“…'The Street is Ours", as one trader once remarked in an interview in Harare, is an essential characteristic of the new geography of resistance, in which street-induced informality is one of the cornerstones. Wegerif and Hebinck (2016) and Wegerif (2020) coined the relationships between and amongst street traders as symbiotic and not necessarily as competitive. The symbiotic nature of their relationships provides actors with the means to defend their operations and their ordering of their vending sites.…”
Section: Discussionmentioning
confidence: 99%
“…'The Street is Ours", as one trader once remarked in an interview in Harare, is an essential characteristic of the new geography of resistance, in which street-induced informality is one of the cornerstones. Wegerif and Hebinck (2016) and Wegerif (2020) coined the relationships between and amongst street traders as symbiotic and not necessarily as competitive. The symbiotic nature of their relationships provides actors with the means to defend their operations and their ordering of their vending sites.…”
Section: Discussionmentioning
confidence: 99%
“…First, close monitoring of price movements and the factors contributing to those movements is paramount, especially during this crisis period. Changes in consumer prices are often claimed to be linked to predatory behavior among traders, motivating government intervention to curb trading activity, as has already been witnessed during the COVID-19 pandemic (Resnick 2020;Wegerif 2020;Gebreamlak 2020). However, the earlier evidence on such predatory behavior is limited (Sitko andJayne 2014, Minten et al 2017) and the findings reported here indicate that the price changes during this pandemic have not been driven by large increases in marketing margins.…”
Section: Discussionmentioning
confidence: 99%
“…One recurring theme was that lockdown measures made it more difficult for small-scale farmers to sell their produce, undermining rural livelihoods and raising concerns that families might be forced into distress land transactions. In South Africa, the closure of street trading, later reversed, was reported to have primarily affected small-scale farmers, who largely rely on informal markets ( Wegerif, 2020 , PLAAS, 2020 ); while reports from Nepal indicated that farmers were having to sell produce at lower prices set by the traders ( Deuja, 2020 ). Meanwhile, urban-to-rural migration by unemployed urban workers in search for new livelihoods in rural areas was expected to increase pressures on agricultural land, potentially displacing tenant farmers and sharecroppers (Choudhury, Ghosh & Sindhi, 2020, on India; Deuja, 2020 , on Nepal).…”
mentioning
confidence: 99%